Variable fonts: possible impacts for information design in digital media and the typography area - Woloszyn, Maíra; Santos Gonçalves, Berenice (InfoDesign, 2024)
Information design is essential in the context of digital media to ensure clarity in communicating messages and facilitate audience comprehension. Various elements, such as typography, are employed to meet this demand. Typography, understood as the field that studies the history, anatomy, design, and use of typefaces, has undergone significant transformations propelled by advancements in digital tools. One of these transformations has been the implementation of variable fonts, which incorporate different widths, weights, slants, and numerous other variations into a single font file. In light of the foregoing, the present study aimed to identify the impact of variable fonts on information design in digital media and the field of typography. To this end, ten interviews were conducted with type designers and experts in variable fonts operating in different contexts and countries. The interviews were transcribed, and data analysis employed the content analysis method and categorical analysis technique, supported by qualitative data analysis software. As a result, it was possible to delineate the characteristics and attributes of variable fonts that contribute to information design in digital media and their implications for typography, particularly in the practice of type design.